(untitled) (Proceedings of Voronezh State University. Series: Geology, 2023)
Introduction: Despite the fact that the petrographic features of the rocks of the Gadabay intrusion and its geological-field descriptions have been studied comprehensively over many years of research, the physical-chemical conditions of the formation of this intrusion have not been studied in detail. Therefore, it is necessary to study the petrochemical properties of the minerals of constituent rocks of the Gadabay intrusion. Methods: In the present study, paired ilmenite and titanomagnetite minerals were studied in order to fill the aforementioned gap. For calculations and interpretations, the results of the bulk chemical analysis and trace element analysis of monomineral samples were used. Images of polished sections of some samples were also presented and discussed. Results and discussion: Ilmenite and titanomagnetite from the rocks of the Gadabay intrusion contain low and moderate concentrations of Ti. High concentrations of titanium in vein rocks can be associated with the enrichment of melts of these rocks with titanium. The concentration of trace elements, such as Ni, Cr, in the composition of titanomagnetite and ilmenite is controlled by fractional crystallization and decreases towards more acidic rocks. There is a positive correlation between FeO and TiO 2 and negative correlation between Fe2O 3 and TiO2. Oxidatively-reducing crystallization medium corresponds to hematite-magnetite (HM) buffer. Conclusions: Based on the results of the study, it can be concluded that the minerals in the rocks crystallized mainly in the upper horizons of the earth’s crust at hypabyssal depths. The environment was mostly oxidative. This was evidenced by the absence of wustite among minals of titanium-ferruginous oxide minerals, which indicates their crystallization in the upper horizons of the earth’s crust.